Identification of bioactive peptide from Oreochromis niloticus skin gelatin - Choonpicharn S. (2017)
© 2015, Association of Food Scientists & Technologists (India). Fish skin, one type of wastes generated from Nile tilapia processing, is still a good source of collagen and gelatin. Bioactive peptides can be obtained from Nile tilapia skin gelatin by trypsin digestion. Trypsin hydrolysate was subsequently purified by gel filtration chromatography. Trypsin A fraction showed the greatest reducing power (5.138 ± 1.060 μM trolox/mg peptide) among all hydrolysate fractions, while trypsin B fraction from gel filtration column was found to exhibit the best radical scavenging and angiotensin-I-converting enzyme (ACE) inhibitory activities 8.16 ± 2.18 μg trolox/mg peptide and 59.32 ± 9.97 % inhibition, respectively. The most active fraction was subjected to MALDI-TOF/TOF MS/MS. After annotation by Mascot sequence matching software (Matrix Science) with Ludwig NR Database, two peptide sequences were identified; GPEGPAGAR (MW 810.87 Da) and GETGPAGPAGAAGPAGPR (MW 1490.61 Da). The docking analysis suggested that the shape of the shorter peptide may be slightly more proper, to fit into the binding cleft of the ACE. However, the binding affinities calculated from the docking showed no significant difference between the two peptides. In good agreement with the in silico data, results from the in vitro ACE inhibitory activity with synthetic peptides also showed no significant difference. Both peptides are thus interesting novel candidates suitable for further development as ACE inhibitory and antioxidant agents from the natural source.